Secreted Osteoclastogenic Factor of Activated T Cells (SOFAT) Is Associated With Rheumatoid Arthritis and Joint Pain: Initial Evidences of a New Pathway - Napimoga, Marcelo Henrique; Dantas Formiga, Weslley Danny; Abdalla, Henrique Ballassini; Trindade-da-Silva, Carlos Antônio; Venturin, Camila Motta; Martinez, Elizabeth Ferreira; Rossaneis, Ana Carolina; Verri, Waldiceu A.; Clemente-Napimoga, Juliana Trindade (Frontiers in Immunology, 2020)
Rheumatoid arthritis (RA) has an inflammatory milieu in the synovial compartment, which is regulated by a complex cytokine and chemokine network that induces continuously degenerative and inflammatory reactions. The secreted osteoclastogenic factor of activated T cells (SOFAT) is a unique cytokine and represents an alternative pathway for osteoclast activation. In this study, we addressed if SOFAT is able to induce joint pain and investigate the presence of SOFAT in a Collagen-induced Arthritis (CIA) model and in human subjects. Here, we found that an intra-articular stimulation with SOFAT (1, 10, 100 or 1000 ng / 10 μl) in the knee joint, significantly decreases the mechanical threshold in the hind paw of mice (p < 0.05). Moreover, after a second injection of SOFAT the decrease of mechanical threshold was sustained for up to 8 days (p < 0.05). In the CIA-model, the immunohistochemical assay of knee joint showed positivity stained for SOFAT, and the mRNA and protein expression of SOFAT were significantly higher in the affected-group (p < 0.05). Besides, the mRNA of RANKL, IL-1β, IL-6, and IL-15 were significantly higher in the affected-group (p < 0.05). Finally, SOFAT was detected in the synovial fluid of RA patients, but not in OA patients (p < 0.05). In conclusion, SOFAT is up-regulated in inflammatory milieu such as RA, but not in non-inflammatory OA. SOFAT may be a novel molecule in the complex inflammatory phenotype of RA.